Empowering Inclusion through Governance and Literacy: Unraveling the Role of Social Capital in Kenya’s Digital Finance Landscape - Brenda Kulola Wakio (Journal of Advanced Research in Social Sciences and Humanities, 2026)
Aim: This study investigates the impact of governance quality and internet penetration on financial inclusion in Kenya, emphasizing the mediating roles of perceived trust in digital financial services and digital literacy, and the moderating role of social capital. The research aims to develop a comprehensive framework that integrates institutional, technological, and behavioral dimensions influencing digital financial inclusion across urban and rural contexts.Methodology: A quantitative research design was employed using data collected from 195 respondents across Kenya’s urban and rural regions. Validated measurement scales were adopted from previous studies, and data were analyzed using ADANCO 2.3 for composite-based Structural Equation Modeling (SEM). The analysis assessed reliability, validity, and structural relationships among constructs through path analysis and bootstrapping procedures.Findings: The results confirmed that both governance quality and internet penetration significantly enhance financial inclusion. Perceived trust and digital literacy mediate these relationships, while social capital moderates the effects of trust and literacy on inclusion. The model demonstrated strong reliability, validity, and explanatory power, with R² values exceeding 0.80.Implications/Novel Contribution: This study extends financial inclusion theory by integrating governance, technology, and social capital perspectives. It offers practical insights for policymakers to promote inclusive finance through governance reforms, digital literacy initiatives, and community-based trust-building strategies.